Зимостойкость некоторых видов рода Sorbus L. в Донбассе - Дацько, А.М. (Донецький ботанічний сад НАН України, 2008)
Изучены анатомические особенности годичных побегов Sorbus persica Hedl., S. domestica L. и
S. aucuparia L. Определены толщина тканей и степень лигнификации ксилемы. Наиболее развиты
покровные и механические ткани у S. aucuparia, годичные побеги полностью вызревшие. У S. persica
наблюдается отставание в развитии тканей и степени одревеснения побегов по сравнению с S. aucuparia.
Отмечена высокая зимостойкость S. domestica и S. aucuparia и более низкая – S. persica. К перспективным
видам отнесены S. domestica и S. aucuparia. Вид – S. persica нецелесообразно вводить в ассортимент
декоративных растений юго-востока Украины. The anatomical peculiarities of annual spears of Sorbus persica Hedl., S. domestica L. and S. aucuparia L. were
studied. The tissue depth and xylem lignification rate were defined. The tissues of S. aucuparia are most developed
and annual spears are fully mature for vegetative period. S. persica lags in terms of tissue development and spear
lignification rate compared to S. aucuparia. S. domestica and S. aucuparia revealed winter resistance at high level,
whereas S. persica demonstrated it at low level. S. domestica and S. aucuparia are treated as perspective, while
S. persica is unreasonable for introduction to the assortment of decorative plants of south-east of Ukraine.